2021
DOI: 10.1002/ase.2067
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Effective Teaching Strategies in Surface Anatomy

Abstract: To become skilled physicians, medical students must master surface anatomy. However, the study of surface anatomy is less emphasized in medical and allied health science curricula, and the time devoted to direct engagement with the human body is limited. This scoping review was designed to answer one research question: "What are the elements and strategies that are effective in teaching surface anatomy?" The review was performed using a five-stage scoping review framework, including research question identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Therefore, a fully online anatomy course cannot ensure students' achievement of necessary learning outcomes (Tg Muda et al, 2021). The adoption of blended learning and the implementation of innovative pedagogical ideas during the pandemic have suggested efficient methods to combine traditional face‐to‐face teaching with online modalities (Abu Bakar et al, 2022; Xiao & Adnan, 2022). However, these approaches' effectiveness and implications for post‐pandemic anatomy curricula must be explored further to ensure their sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a fully online anatomy course cannot ensure students' achievement of necessary learning outcomes (Tg Muda et al, 2021). The adoption of blended learning and the implementation of innovative pedagogical ideas during the pandemic have suggested efficient methods to combine traditional face‐to‐face teaching with online modalities (Abu Bakar et al, 2022; Xiao & Adnan, 2022). However, these approaches' effectiveness and implications for post‐pandemic anatomy curricula must be explored further to ensure their sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been increased recent focus on active, experiential learning activities to improve understanding of anatomy, [86][87][88] there has been limited development of approaches to support visuospatial and metacognitive skills in anatomy learning and assessments. 8,28,89 Here, this area is addressed through presenting a description and evaluation of a novel Haptic Surface Painting (HSP) approach.…”
Section: Haptic Surface Paintingmentioning
confidence: 99%
“…Previous studies provided evidence of successful surface anatomy initiatives including body painting, 71,72 learning through ultrasound imaging and scanning sessions, 73,74 and clinical-applied teaching sessions. 75 Abu Bakar et al 76 performed a scoping review to determine elements and strategies that were effective in teaching surface anatomy and found that contextualized teaching, experiential learning, and learning facilitation (comprising the teachers' role and technology-enhanced teaching) to be three main themes. Finally, an expansion of surface anatomy content within gross anatomy could also provide an additional opportunity for interprofessional education (e.g., physical therapy students assisting medical students with musculoskeletal examination training).…”
Section: Surface Anatomymentioning
confidence: 99%